Ecological assessment of the different types water bodies of the Sharapov Shar Bay basin in terms of the chlorofill “a” concentration (the Middle Yamal) - Margarita I. Yarushina; Valery F. Mukhutdinov; Leonid N. Stepanov (Water Sector of Russia: PROBLEMS, TECHNOLOGIES, MANAGEMENT, 2024)
Under the conditions of intense development and use of the hydrocarbon fields, the minimization of negative consequences for aquatic ecosystems has become the most important issue. The article presents results of the studies of phytoplankton and the chlorofill “a” content in the different types of water bodies on the territory of the Kruzenstern gas-condensate field located at the Middle Yamal western bank.